Svetlana Slapšak’s Feminist Essay: A Polygraph of Contemporary Culture - Koch, Magdalena (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The article discusses the problem of the theory and practice of contemporary Serbian feminist essay. The text indicates how – at the turn of the 21st century – the essay participated in the reading of the nationalist culture of fear during the breakup of Yugoslavia, how it became the tool for creating an analytical and methodological platform and a means of quick anthropological and cultural diagnoses, as well as a form of transfer of social or philosophical notions. This new strategy of the essay was illustrated through the examples of books by Svetlana Slapšak, a leading figure of the (sub)genre in the Serbian culture, a professor of cultural anthropology, classical philologist, and feminist critic: Mala crna haljina. Eseji o antropologiji i feminizmu (1993/2007, Little Black Dress. Essays on Anthropology and Feminism), Ženske ikone XX veka (2001, Female Icons of the 20th Century), Ženske ikone antičkog sveta (2006, Female Icons of the Antiquity), Antička miturgija: žene (2013, Antique Mythurgy: Women). It becomes clear that one of the trends of the contemporary essay in the Serbian and post-Yugoslav cultures is the application of the genre in the spirit of modern engaged humanities and textual intervention.